Pneumatically Actuated Active Suspension System for Reducing Vehicle Dive and Squat - Ahmad, Fauzi; Khisbullah , Hudha; Harun, Mohd Hanif (UTM, 2009)
This manuscript provides a detailed derivation of a full vehicle model, which may be used to simulate the behavior of a vehicle in longitudinal direction. The dynamics of a 14 degrees of freedom (14- DOF) vehicle model is derived and integrated with an analytical tire dynamics namely Calspan tire model. The full vehicle model is then validated experimentally with an instrumented experimental vehicle based on the driver input from brake or throttle. Several transient handling tests are performed, including sudden acceleration test and sudden braking test at constant speed. Comparisons of the experimental result and model response with sudden braking and throttling imposed motion are made. The results of model validation showed that the trends between simulation results and experimental data are almost similar with acceptable error. An active suspension control system is developed on the validated full vehicle model to reduce unwanted vehicle motions during braking and throttling maneuver. A proportional-integral-derivative (PID) scheme integrated with pitch moment rejection loop is proposed to control the system. In presented scheme the result verify improved performance of the proposed control structure during braking and throttling maneuvers compared to the passive vehicle system. It can also be noted that the additional pitch moment rejection loop is able to further improve the performance of the PID controller for the system. The proposed controller will be used to investigate the benefits of a pneumatically actuated active suspension system for reducing unwanted vehicle motion in longitudinal direction.